24/#263 Cost study of plasmajet surgical device versus conventional cytoreductive surgery in advanced-stage ovarian cancer patients. (4th December 2022) - Boer, Gatske Nieuwenhuyzen-De; Geraerds, Sandra; Linden, Marieke Van Der; Polinder, Suzanne; Beekhuizen, Heleen Van
Abstract : Objectives: Adjuvant use of Neutral Argon Plasma (PlasmaJet® Surgical Device) during cytoreductive surgery (CRS) for advanced-stage epithelial ovarian cancer (EOC) improves surgical outcome. The aim of this study is to examine the costs of adjuvant use of the PlasmaJet during surgery compared to conventional cytoreductive surgery in advanced-stage EOC. Methods: The patients were randomly assigned to surgery with or without the PlasmaJet. Analysis of the intra – and extramural healthcare costs were performed. Costs were divided in three categories: Costs of the diagnostic phase (T1), inpatient care up to discharge, including costs of surgery (T2), and outpatient care including chemotherapy until six weeks after the last cycle of chemotherapy (T3). Results: Overall, 327 patients underwent cytoreductive surgery (surgery with PlasmaJet: N=157; conventional surgery: N=170). The mean total health costs were significantly higher for CRS with adjuvant use of PlasmaJet compared to conventional CRS (€19, 414 vs. €18, 165, p=0.017). Costs are divided in costs of the diagnostic phase (€2, 034 vs. €1, 974, p=0.890), costs of inpatient care (€10, 956 vs. €9, 556, p=0.003) and costs of outpatient care (€6, 417 vs. €6, 628, p=0.147). Conclusions: Mean total health care costs of the use of PlasmaJet in CRS were significantly higher than for conventional CRS. This difference is fully explained by the additional surgery costs of the use of PlasmaJet. However, surgery with the use of the PlasmaJet leads to a significant higher percentage of complete CRS and a halving of stomas. A cost-effectiveness analysis will be performed once survival data are available.